Comparison of the effects of subconjunctival and topical anti-VEGF therapy (bevacizumab) on experimental corneal neovascularization - Ozdemir,Ozdemir (2014)
Purpose: To compare the effects of bevacizumab applied either subconjunctivally or topically, in a rat model of corneal neovascularization induced by alkali burn. Methods: The right corneas of 24 Wistar-Albino rats were cauterized with silver nitrate sticks. The rats were divided randomly and equally into three groups: no treatment control (n=8), subconjunctival bevacizumab treatment (n=8), and topical bevacizumab treatment (n=8). Immediately following cauterization, the subconjunctival group was treated with a 0.05 ml (1.25 mg) bevacizumab subconjunctival injection. The topical group was treated with 10 mg/ml bevacizumab twice daily, and the control group received subconjunctival saline injections twice daily. The burn stimulus and neovascularization scores were evaluated using a technique previously described by Mahoney and Waterbury. Digital photographs were obtained before the eyes were enucleated and corneal sections were then analyzed by histopathology. Results: The mean burn stimulus score was 1.86 ± 0.6 and there was no statistical difference between the groups (p=0.730). The mean neovascularization scores in the subconjunctival and topical bevacizumab groups were statistically lower than the control group (p<0.05). The mean percentage area of corneal neovascularization was 82.5 ± 22.1 in the control group, 42.7 ± 15.0 in the subconjunctival group, and 55.8 ± 18.2 in the topical group. The differences between the control and treatment groups were statistically significant (p<0.05). Histopathology showed that the treatment groups presented less neovascularization, inflammation, and fibroblast activity than the control group (p<0.05). Conclusions: This study demonstrates that both subconjunctival and topical administrations of bevacizumab inhibit corneal neovascularization and decrease inflammation and fibroblast activity in a rat model of corneal neovascularization induced by alkali burn.